2007
DOI: 10.1152/ajpgi.00225.2006
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular calcium-sensing receptor reciprocally regulates the secretion of BMP-2 and the BMP antagonist Noggin in colonic myofibroblasts

Abstract: Peiris D, Pacheco I, Spencer C, MacLeod RJ. The extracellular calcium-sensing receptor reciprocally regulates the secretion of BMP-2 and the BMP antagonist Noggin in colonic myofibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…calcium-sensing receptor activation (29,55). We showed a marked increase of BMP2 expression in TNBS colitis and its reduction following BMP7 treatment.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…calcium-sensing receptor activation (29,55). We showed a marked increase of BMP2 expression in TNBS colitis and its reduction following BMP7 treatment.…”
Section: Discussionmentioning
confidence: 71%
“…It was shown that upregulated CTGF inhibits BMP4 and BMP7 activity leading to deficiency of BMP signaling (1,53,64). Also, noggin has a reciprocal relationship with BMP2 in colonic myofibroblasts and coexpression with BMP4 in atherosclerotic lesions of human coronary arteries (13,55). Overexpression of noggin caused the absence of Smad 1/5/8 signaling and a disease similar to JP, whereas its downregulation showed opposite effect on different types of arthritis (27,43).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitation of the phosphorylation of p44/42 was done using an ImageQuant and a Personal Densitomenter (Molecular Dynamics). HT-29 cells were treated as previously described (33,38).…”
Section: Methodsmentioning
confidence: 99%
“…Several candidate regions of the CaSR nucleotide sequence were used to generate small interfering (si)RNA duplex constructs as previously described (33,38). We first found 13 potential siRNA target sites in the extracellular domain of the CaSR.…”
Section: Methodsmentioning
confidence: 99%
“…4). It was also shown that activation of extracellular calcium-sensing receptor (CaSR), expressed on the epithelia of the GI tract and myofibroblasts, downregulated BMP4 and noggin expression and raises the effective concentration of BMP2 leading to increased intestine repair and barrier development (Peiris et al, 2007). …”
Section: Bmps and Their Signaling Pathway In The Normal Gastrointestimentioning
confidence: 99%